Optimization of the method for the determination of diethyl sulfate at workplaces - Joanna Kowalska; Anna Jeżewska (Nofer Institute of Occupational Medicine, 2018)
Background Diethyl sulfate (DES) is a substance classified to the group of carcinogens. The value of maximum admissible concentration for this substance in workplace air is not specified in Poland. Due to the use of DES in domestic companies there is a need to develop a sensitive method for the determination of diethyl sulfate in the work environment. Material and Methods Studies were performed using gas chromatography (GC) technique. An Agilent Technologies chromatograph, series 7890A, with a mass selective detector (5975C, Agilent Technologies, USA) was used in the experiment. Separation was performed on a capillary column with Rtx-5MS (30 m × 0.25 mm × 0.25 μm) (Restek, USA). The possibility of using sorbent tubes filled with activated carbon (100 mg/50 mg), silica gel (100 mg/50 mg) and Porapak Q (150 mg/75 mg) for absorption of diethyl sulphate was investigated. Results The method of sampling air containing diethyl sulfate was developed. Among the sorbents to absorb DES Porapak Q was chosen. Determination of the adsorbed vapor includes desorption of DES, using dichloromethane/methanol mixture (95:5, v/v) and chromatographic analysis of so obtained solution. Method is linear (r = 0.999) within the investigated working range of 0.27- -5.42 μg/ml, which is an equivalent to air concentrations 0.0075-0.15 mg/m 3 for a 36 l air sample. Conclusions The analytical method described in this paper allows for selective determination of diethyl sulfate in the workplace air in the presence of dimethyl sulfate, ethanol, dichloromethane, triethylamine, 2-(diethylamino)ethanol, and triethylenetetramine. The method meets the criteria for performing procedures aimed at measuring chemical agents, listed in EN 482. Med Pr 2018;69(3):291-300